2020
DOI: 10.1002/cbf.3584
|View full text |Cite
|
Sign up to set email alerts
|

ALDH5A1 acts as a tumour promoter and has a prognostic impact in papillary thyroid carcinoma

Abstract: Thyroid cancer is the most common endocrine carcinoma, with papillary thyroid carcinoma (PTC) accounting for 80%‐90% of thyroid cancers. Accumulating studies reported that mitochondria plays an important role in the regulation of cell proliferation. ALDH5A1, may function as an oncogene or tumour suppressor in various human cancers, and the role of ALDH5A1 in PTC is still unclear. The aim of this study was to investigate the clinical significance of ALDH5A1 expression and its functions in PTC. In this present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Results will be critical for future development of AAV vectors that require incorporating cell-specific promoters [105]. Limiting SSADH restoration to relevant cell populations is particularly important from a metabolic homeostasis standpoint, given that aberrant aldh5a1 gene activities have been linked to oncogenesis [106,107]. This novel aldh5a1 STOP/STOP mouse will be useful as a platform to develop other novel SSADH-targeted strategies.…”
Section: The Novel Ssadhd Mouse Model Aldh5a1 Stop/stopmentioning
confidence: 99%
“…Results will be critical for future development of AAV vectors that require incorporating cell-specific promoters [105]. Limiting SSADH restoration to relevant cell populations is particularly important from a metabolic homeostasis standpoint, given that aberrant aldh5a1 gene activities have been linked to oncogenesis [106,107]. This novel aldh5a1 STOP/STOP mouse will be useful as a platform to develop other novel SSADH-targeted strategies.…”
Section: The Novel Ssadhd Mouse Model Aldh5a1 Stop/stopmentioning
confidence: 99%
“…Nevertheless, some of the hub genes in our miRNA–mRNA network were poorly studied and have not been reported in RF before. The expression changes of Slc1a1 , Myo5a , and Aldh5a1 were known to affect cancer cell proliferation migration, invasion, and metastasis and may be critical for carcinoma pathophysiology ( Tian et al, 2017 ; Ergün et al, 2019 ; Tomic et al, 2020 ; Deng et al, 2021 ). In addition, a previous study revealed the correlation between the loss of Aldh5a1 and the presence of epithelial–mesenchymal transition ( Hilvo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genetic alteration of ALDH5A1 and ABAT causes inherited disorders of gamma-aminobutyric acid (GABA) metabolism and may develop Alzheimer's Disease and paranoid schizophrenia [40,71,72]. Moreover, previous studies show that the decreased expression of ALDH5A1 in patients with ovarian cancer or papillary thyroid carcinoma may lead to a poor prognosis [73,74]. The interaction of ABAT and ALDH5A1 in tumor treatments may have a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%